Quality Education: Perception of Students: With reference to the Higher Secondary Level - Raizada, Ramakar (JOURNAL OF INDIAN EDUCATION, 2008)
Students are ultimate stakeholders and direct consumers of the education system who feel and judge the quality of education. Their perception and feelings for quality education may go a long way in improving the system. National Policy on Education (1986), Programme of Action (1992), National Curriculum Framework (2005), etc. have called for substantial improvement in the quality of school education. But, how students perceive the concept of quality education and what expectations they have in this regard is an important issue. The paper conceptualises students’ perception about their school environment and facilities of education with their likings and reasons for weakness in different school subjects at higher secondary level. The paper also suggests changes in classroom practices and shift in position of the teacher from transmitter of information to facilitator for construction of knowledge in the minds of students.